(untitled) (Baghdad Science Journal, 2015)
Bioaccumulation of heavy metals in the terrestrial invertebrates in Al-Jadriyia district Baghdad- Iraq were investigated. Forth terrestrial invertebrates snails, slug, isopods, and diplopods , were selected for this study. The results showed that all invertebrate groups have the ability in accumulate considerable amounts of heavy metals. Higher levels of zinc and copper were observed in the isopods specimens, it’s about ( 60.50±0.58 ) and ( 96.00±0.58 ) ppm respectively , while higher levels of lead were observed in the diplopods specimens ,it’s about ( 23.00±1.15 ) ppm ,but the higher levels of both iron and cadmium were observed in snail specimens , it’s about ( 590.00±1.15 ) and ( 9.50±1.15 ) ppm respectively .but the higher level between all heavy metals concentration in soil specimens were recorded in iron , zinc , lead, copper, and cadmium, it’s about ( 8000.00±1.73 ) , ( 33.00±1.73 ) , ( 30.00±1.15 ) , ( 20.00±0.58 ) , and ( 10.00±1.73 ) ppm respectively .The correlation values show that most significant in some metals , while they show that non significant between in other metals .